Gamma power abnormalities in a Fmr1-targeted transgenic rat model of fragile X syndrome - Kozono, Naoki; Okamura, Ai; Honda, Sokichi; Matsumoto, Mitsuyuki; Mihara, Takuma (Scientific Reports, 2020)
Fragile X syndrome (FXS) is characteristically displayed intellectual disability, hyperactivity, anxiety, and abnormal sensory processing. Electroencephalography (EEG) abnormalities are also observed in subjects with FXS, with many researchers paying attention to these as biomarkers. Despite intensive preclinical research using Fmr1 knock out (KO) mice, an effective treatment for FXS has yet to be developed. Here, we examined Fmr1 -targeted transgenic rats ( Fmr1 -KO rats) as an alternative preclinical model of FXS. We characterized the EEG phenotypes of Fmr1 -KO rats by measuring basal EEG power and auditory steady state response (ASSR) to click trains of stimuli at a frequency of 10–80 Hz. Fmr1 -KO rats exhibited reduced basal alpha power and enhanced gamma power, and these rats showed enhanced locomotor activity in novel environment. While ASSR clearly peaked at around 40 Hz, both inter-trial coherence (ITC) and event-related spectral perturbation (ERSP) were significantly reduced at the gamma frequency band in Fmr1 -KO rats. Fmr1 -KO rats showed gamma power abnormalities and behavioral hyperactivity that were consistent with observations reported in mouse models and subjects with FXS. These results suggest that gamma power abnormalities are a translatable biomarker among species and demonstrate the utility of Fmr1 -KO rats for investigating drugs for the treatment of FXS.